Symbiotic diversity of Portunus pelagicus (Linnaeus, 1758) in Vietnam - implication for species and geographic variations - Binh Thuy Dang; Oanh Thi Kieu Le; Sang Quang Tran; Oanh Thi Truong (Fisheries and Aquatic Sciences)
A total of 479 wild blue swimming crabs, Portunus pelagicus were collected from north to south along the Vietnam coastline. Symbiont species of the crabs were determined using morphological and genetic characters, and the temporal and spatial variation pattern in the symbiont were examined. For the symbionts load, 17.95% of crabs were uninfected, 46.13% infected by 1–2 species, 27.33% infected by 3–5 species, and 8.56% infected by more than 5 species. Among the 18 symbiont species found, 6 comprise unidentified, and three probably new host records. Crabs from the center of Vietnam had 17 symbiont species, those from the north had 12, and those from the south had 13. The most common symbionts were pedunculate barnacles, Octolasmis angulata, its congeners (O. warwickii and O. neptuni), and the protozoan ciliate, Zoothamnium chlamydis. The nemertean, Carcinonemertes mitsukurii and the copepod, Choniosphaera indica are well-known egg eating parasites. Verrillactis paguri and Electroma papilionacea were exclusively found in central Vietnam and Triticella flavar occurred in the north only. The most common symbionts differed in prevalence and mean intensity across geographic localities, and sex differences were found. Epistylis sp. and C. mitsukurii differed in prevalence and mean intensity in the two host sexes, whereas O. angulata and O. warwickii intensity and prevalence, respectively, differed. Prevalence and mean intensity were positively correlated with crab sizes for O. angulata and C. mitsukurii. Combined host features (distribution, sex and size) against symbiont diversity were also detected to be significantly different. Considering the host-symbiont associations, diversity indexes did not show a clear connection between host features and symbiotic diversity.